Answer:
3%
hope this helps!
Step-by-step explanation:
Answer:
Step-by-step explanation:
<h2>C A L C U L A T I O N S</h2>
Once you add and simplify you’re answer will be
- 5/(x+3)(x-2)
Answer:
<h2>22.0544</h2>
Step-by-step explanation:
3.2 × 6.892 = 22.0544
I'm always happy to help :)
Answer:
x = 1.47 or x = -7.47
Step-by-step explanation:
x²+6x+9=20
This is a quadratic equation
x²+6x+9-20=0
x²+6x-11=0
Step 1 : Write the quadratic formula
x = <u>-b±√b²-4(a)(c)</u>
2a
Step 2 : Substitute values in the formula
a = 1
b = 6
c = -11
x = <u>-6±√6²-4(1)(-11)</u>
2(1)
x = <u>-6±√80</u>
2
x = -3 + 2√5 or x = -3 - 2√5
x = 1.47 or x = -7.47
!!